Treatment of Thoracic Outlet Syndrome Complications Assisted with a Cerebral Embolism Protection Device - Marina Ansuategui-Vicente; Yolanda Tapia-Lopez; Cristina Cases-Perez; Gabriela Ibarra-Sanchez; Ania Garcia Gutierrez; Jose-Antonio Gonzalez-Fajardo (Methodist DeBakey Cardiovascular Journal)
We report a case of a stroke and upper limb ischemia in a 27-year-old female secondary to a right cervical rib and retrograde thromboembolization. Follow-up showed complete patency of the vessels after thrombectomy and internal carotid artery stenting followed by transbrachial embolectomy performed with a cerebral protection device. The cervical rib was surgically removed to prevent additional events.